PENGARUH PENYALURAN KREDIT TERHADAP PROFITABILITAS DENGAN RISIKO KREDIT SEBAGAI VARIABEL PEMODERASI - Dhian Andanarini Minar Savitri; Harum Indinah Diananingsih (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2016)
This study analyzes the effect of bank lending to profitability by usingcredit risk as a moderating variable. The data used in this study isconventional banking listed on the IDX period 2011-2014. The results ofthis study indicate that loan disbursement negatively affects profitability,credit risk negatively affect profitability and credit risk can not moderate theeffect of credit distribution on the profitability of banks in Indonesia.Keywords: lending ratio, credit risk, profitability